PHYSICAL THERAPY FOR DANCERS - Rabcheniuk, S. V.; Hrytsenyuk, R. A.; Voloshyna, L. P. (Rehabilitation and Recreation, 2025)
Purpose is to develop and implement a physical therapy programme for female dancers participating in the Standard programme of sports ballroom dancing, aimed at improving the functional condition of the cer-vical and thoracic spine, reduce discomfort and pain, and prevent overload and injuries to the musculoskeletalsystem that occur during training and competitions. Materials and Methods. Theoretical methods of scientif- ic research were applied, namely: analysis, synthesis, abstraction, concretisation, induction, deduction, logical methods, and systemic methods. Results. The implementation of the developed physical therapy programme contributed to achieving positive dynamics in the functional state of the cervical spine in dancers performingclassical dance elements. The results obtained indicate the effectiveness of the implemented set of measures.The results of repeated functional testing showed a significant reduction in pain intensity in the cervical-collar zone, confirming the effectiveness of the techniques used (massage, soft manual therapy, physiotherapy, relax- ation techniques). Most of the programme participants showed an increase in the range of active and passivemovements in the cervical spine, indicating improved soft tissue elasticity and reduced muscle tension. Thanks to the systematic performance of isometric exercises and exercises to stabilise the torso, an increase in the tone of the deep muscles of the neck and torso was noted, which ensured improved postural control and a reduced risk of overload during the training process. The use of exercises on unstable surfaces and with biofeedback improved symmetry and posture control, which is important for the aesthetics of dance movements. The overalllevel of physical performance and adaptation to specific dance loads also improved, confirming the preventive and training effectiveness of the programme. During the final stage, a reduction in muscle rigidity, asymmetry ofmuscle tone and functional blocks in the cervical and thoracic spine was observed. Conclusions. The results ofthe study demonstrated the effectiveness of implementing an individualised physical therapy programme aimedat improving the functional state of the cervical spine in dancers who systematically perform classical dance elements. The combination of therapeutic exercises, isometric loads, soft manual therapy, stretching, massageand physiotherapy techniques made it possible to reduce the intensity of pain, improve mobility and restore muscle-postural balance. It was found that regular physical therapy improved the flexibility and mobility of thecervical and thoracic spine, increased the strength of the neck, shoulder girdle and back muscles, and developed postural control skills, which are critical for ensuring technical accuracy and safe execution of dance movements.